2016
DOI: 10.1039/c6ra06122b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of kinetic inhibitors for clathrate hydrate using unidirectional growth apparatus

Abstract: We study the formation of tetrahydrofuran (THF) clathrate hydrate from polyvinylpyrrolidone (PVP) aqueous solution as a function of growth rate V and adsorbed PVP concentration c using the unidirectional growth technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 15 publications
(27 reference statements)
0
37
0
Order By: Relevance
“…The present study employed the same experimental methods that we reported previously; 28 we summarised the setup as follows.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study employed the same experimental methods that we reported previously; 28 we summarised the setup as follows.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…From measurements of Dx i (t) at steady state, we can calculate the supercooling due to the KHI additive (DT i ). 28 In our previous study, we calculated the temperatures at each position of the sample cell based on the temperature gradient, and the distance from each thermo-block. DT i was calculated using the simple formula in (1):…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Many studies focused on the changing trend of ow parameters (e.g., P, T, ow rate, pressure drop, hydrate particle size, inhibitor, hydrate formation induction, supercooling degree etc. [8][9][10][11][12] ), and other studies focused on the relationship between supercooling degree and kinetic inhibitor concentration, 13 but hydrate morphology evolvement and liquid stratication phenomena during the plugging process are less involved.…”
Section: Introductionmentioning
confidence: 99%
“…Clathrate hydrates are crystalline solid compounds that exist widely in ocean sediments, permafrost regions, and comets and on certain planets. [1][2][3][4][5][6][7][8][9] Interest in clathrate hydrates arose due to of two aspects. First, their ability to store methane on a large scale, both underground and in the ocean, means that they might become a major source of energy in the future.…”
Section: Introductionmentioning
confidence: 99%